Relative efficiency of maximum likelihood and other estimators in a nonlinear regression model with small measurement errors - Alexander Kukush; Hans Schneeweiss (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2004)
We compare the asymptotic covariance matrix of the ML estimator in a nonlinear measurement error model to the asymptotic covariance matrices of the CS and SQS estimators studied in Kukush et al (2002). For small measurement error variances they are equal up to the order of the measurement error variance and thus nearly equally efficient.
urn:nbn:de:bvb:19-epub-1766-8
Keywords: 519; Measurement Errors; Maximum Likelihood; Efficiency; Small Error Variance